2018
DOI: 10.1007/s11136-018-1827-2
|View full text |Cite
|
Sign up to set email alerts
|

Life for patients with myelofibrosis: the physical, emotional and financial impact, collected using narrative medicine—Results from the Italian ‘Back to Life’ project

Abstract: Better understanding of the personal life of MF patients and their families could improve the relationships between health workers and patients, resulting in better focused healthcare pathways and more effective financial support to maintain patients in their social roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The impact of providing informal care on a caregivers' employment was measured in eight studies by valuing the loss of income resulting from absence from work and/or productivity loss while at work (Guerriere et al, ; Jassem, Penrod, Goren, & Gilloteau, ; Jeon & Pohl, ; Palandri et al, ; Syse et al, ; Van Houtven et al, ; Wan et al, ; Yu et al, ). Reduced productivity while at work due to providing care (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of providing informal care on a caregivers' employment was measured in eight studies by valuing the loss of income resulting from absence from work and/or productivity loss while at work (Guerriere et al, ; Jassem, Penrod, Goren, & Gilloteau, ; Jeon & Pohl, ; Palandri et al, ; Syse et al, ; Van Houtven et al, ; Wan et al, ; Yu et al, ). Reduced productivity while at work due to providing care (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The cost of care time was valued by measuring the time spent providing informal care, including time spent on ADL, instrumental activities of daily living (IADL), household activities or time spent with the care recipient at the hospital or medical appointments (Bayen et al, ; Guerriere et al, ; Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Hanly, Céilleachair, Skally, O'Leary, Staines, et al, ; Hanly, Maguire, Balfe, O'Sullivan, & Sharp, ; Palandri et al, ; Van Houtven et al, ; Yabroff & Kim, ; Yu et al, ). Studies using the PGA method to value care time reported the value of informal care as $975 to $19,112 per month with a mean of $4,809 per month ( SD = $6,441; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies addressing the extent of spouse wage losses differed in the types of cancer considered (eg, any type, lung cancer, and colorectal cancer), included mixed stages of disease or focused only on advanced disease, and were conducted in countries with different insurance and health care systems (eg, Canada, the United States, China, and Norway) . In these studies, wage loss estimates were calculated for different time periods (range, 1 day of work to 8 years after diagnosis) and with various data sources (self‐reported data and administrative databases) and methods of valuing time lost from work.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent systematic 9 and scoping reviews 10 have reported that cancer negatively affects the employment of spouses of patients with cancer in terms of decreased productivity and work absences. Although a few studies have estimated how decreased productivity and work absences translate into spouses' wage losses, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] most have focused on cancers other than breast cancer 17,18,[24][25][26] or mixed groups including breast cancer with varying disease stages 11,12,[14][15][16]23 Cancer March 1, 2020 or only advanced disease, 13,[19][20][21][22] and this makes it impossible to isolate specifically the effect of nonmetastatic breast cancer on spouse wage losses. Thus, information is needed to understand the extent to which spouses experience wage losses as a result of nonmetastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%